Comparative Study of the Antennae of Dendroctonus rhizophagus and Dendroctonus valens (Curculionidae: Scolytinae): Sensilla Types, Distribution and Club Shape. (1st November 2014) - López, María Fernanda; Armendáriz-Toledano, Francisco; Sámano, Jorge E Macías; Shibayama-Salas, Mineko; Zúñiga, Gerardo
Abstract: We compared the antennae of two sibling bark beetle species, Dendroctonus rhizophagus Thomas and Bright and Dendroctonus valens LeConte, to identify biologically and taxonomically relevant differences. Specifically, we characterized the diversity of sensilla types by using environmental scanning electron microscopy, quantified the abundance and distribution of the different types of sensilla on the antennal club, and characterized club shape through multivariate and geometric morphometric analyses. We identified four classes of sensilla in both species: chaetica, fluted, trichodea (three distinct types), and basiconica (long and short). ANOVA and MANOVA demonstrated that the number and distribution of sensilla with the potential for chemoreception (i.e., short and long basiconica) differed between species and sexes. Notably, the long sensilla basiconica in the third sensory band were clustered in D. rhizophagus but not in D. valens. Geometric morphometric analysis using 27 landmarks showed that antennal club shape differed significantly between the two species and was not correlated with antennal size. The shape differences were associated with the number and distribution of sensilla.